(untitled) (Research, Society and Development, 2022)
Through this research, the objective was the use of geoprocessing to characterize the areas of implementation of dams distributed in areas with agricultural uses, in addition to evaluating the perception of producers regarding the supply of water. The geographic coordinates (vector points) of dam construction sites on rural properties in the municipalities of Corumbá de Goiás, Abadiânia, Alexânia and Silvânia, GO were used. The characterization of these little dams, and their area of influence, was applied by geoprocessing techniques with products such as: land use and cover, soil classes, hypsometry and terrain slope. All information was entered and analyzed using the QGIS 3.10 software. To assess the perception of producers regarding the supply of water in springs and the dry period, a questionnaire was applied. The installation of dams has been distributed in areas with steep slope of the land, ramp length less than 100m (in most properties), the largest number of dams implemented were in areas with greater slope and ramp length, and soils of the class of Oxisols. The use of satellite images, morphometric products, and geoprocessing techniques indicates the potential use of these tools for application in soil and water conservation areas. According to the producers, the barraginhas provide benefits for agriculture by increasing the supply of water in source of the river and in periods of drought in local rivers.